Opportunities for the development of dark tourism in Ukraine - Lushchyk, Mariya; Mamchur, Olha (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Formulation of the problem. Every year there are new types of tourism and, accordingly, new directions of tourist travel. Among such areas is dark tourism, which, although it exists in the modern sense of the term for no more than 25 years, but already plays an important role in the modern tourism industry. We believe that this type of tourism has all the opportunities and prospects for further development in Ukraine.Analysis of recent research and publications. The issue of «dark» tourism is still insufficiently studied in the scientific literature, but has long been of some public interest, so we consider research on «dark» tourism in Ukraine relevant and timely. Based on the analysis of domestic and foreign scientific literature, the article describes the main approaches to the interpretation of the concept of «dark» tourism. The distinctive features that determine the content of «dark» tourism, its classification with a brief description of thematic varieties: mystical tourism, necropolis tourism, thanatourism and disaster tourism. The key reasons for tourists' interest in dark tourism (curiosity, search for novelty, historical memory and respect for cultural heritage, the role of the media and the emotional factor) are identified and the motivation of potential «dark» tourists is described.Formulation of the purpose of the article. The purpose of the work is to specify the content of the concept of dark tourism, justify the specific structure of dark tourism, monitor the resource base for the development of dark tourism in Ukraine, identify the problems of its implementation and develop proposals for their solution.Presentation of the main research material. The preconditions for the development of dark tourism in Ukraine are analyzed. The resource base of this type of tourism is investigated: on the basis of monitoring of «dark» places and locations of Ukraine 127 potentially popular for tourists objects are selected: medieval castles and fortresses, dungeons, thematic museums, prisons, cathedrals, ancient settlements, cemeteries, zones, battlefields, battlefields, etc., which can be used in the development of new tourism products. The geographical and thematic structuring of these objects is carried out, regularities in their geospatial organization are revealed. The most interesting objects of dark tourism of each of the macro-regions of Ukraine are singled out and their brief description is given.Problems and prospects of the development of "dark" tourism. An analytical review of opportunities and threats to the development of dark tourism in Ukraine with the help of SWOT-analysis, substantiates the problems of development of this type of tourism and presents possible ways to solve them.Proposed measures to popularize dark tourism in Ukraine. Measures for popularization and commercialization of dark tourism in Ukraine are offered, in particular: 1) monitoring of «dark»  locations in Ukraine for their suitability for visiting by tourists; 2) creation of an interactive map of dark places of Ukraine; 3) the use of foreign experience in the organization of «dark» tours by domestic tourism enterprises; 4) organization of thematic events − cultural events, competitions, quests, festivals, educational tours, etc .; 5) creation of a web page with information about dark places of Ukraine and relevant tours, launch of the YouTube channel «Mystical Ukraine»; development of profile mobile applications.